2008
DOI: 10.1111/j.1939-3938.2006.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Research and Evaluation of Clinical Nurse Mentoring: Implications for the Forensic Context

Abstract: The impact of mentoring programmes was examined in this extensive literature review. The effectiveness of such programs was considered for both the general clinical nursing and clinical forensic nursing environments. No literature discussing clinical nurse mentoring within forensic settings was discovered during the review, thus implications for this unique context are drawn from the current available literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Norman and Parrish reported: "if nurses are to be retained in the prison service, induction and support for new staff is essential" (p.654). Similarly, in a review article by Cashin and Potter (2006) Cashin and Potter also noted that mentoring was beneficial to both the mentor and the mentee. Therefore, the benefits of supporting such programming in the correctional setting would be two-fold: first, nurses new to corrections would be better supported to practice correctional nursing; and secondly, mentorship may provide the professional growth and development that participants in this study sought, as described in essential structure 8.…”
Section: Supporting the Professional Role Of New And Current Nurses In Correctionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Norman and Parrish reported: "if nurses are to be retained in the prison service, induction and support for new staff is essential" (p.654). Similarly, in a review article by Cashin and Potter (2006) Cashin and Potter also noted that mentoring was beneficial to both the mentor and the mentee. Therefore, the benefits of supporting such programming in the correctional setting would be two-fold: first, nurses new to corrections would be better supported to practice correctional nursing; and secondly, mentorship may provide the professional growth and development that participants in this study sought, as described in essential structure 8.…”
Section: Supporting the Professional Role Of New And Current Nurses In Correctionsmentioning
confidence: 89%
“…Dale and Woods (2002) reported that correctional nurses found that physical aspects of the secure environment were "awesome" and "intimidating" at times. The importance of mentoring and comprehensive orientation for correctional nurses is also strongly supported in the literature (Cashin & Potter, 2006;Maroney 2005;Norman & Parrish, 1999). Norman and Parrish reported: "if nurses are to be retained in the prison service, induction and support for new staff is essential" (p.654).…”
Section: Supporting the Professional Role Of New And Current Nurses In Correctionsmentioning
confidence: 95%